2014
DOI: 10.1111/jth.12711
|View full text |Cite
|
Sign up to set email alerts
|

Role of inorganic nitrate and nitrite in driving nitric oxide–cGMP‐mediated inhibition of platelet aggregation in vitro and in vivo

Abstract: To cite this article: Apostoli GL, Solomon A, Smallwood MJ, Winyard PG, Emerson M. Role of inorganic nitrate and nitrite in driving nitric oxide-cGMP-mediated inhibition of platelet aggregation in vitro and in vivo. J Thromb Haemost 2014; 12: 1880-9.Summary. Background: Nitric oxide (NO) is a critical negative regulator of platelets that is implicated in the pathology of thrombotic diseases. Platelets generate NO, but the presence and functional significance of NO synthase (NOS) in platelets is unclear. Inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 58 publications
5
30
0
2
Order By: Relevance
“…Given that a background DAF fluorescence was also present in unstimulated platelets in suspension and that some residual DAF fluorescence was observed in platelets adhering to collagen under flow after incubation with L-NMMA, it is possible that NO came in part from the reduction of inorganic nitrite within platelets. 41 We also showed that platelet NO production by individual platelets temporally follows the increase in cytosolic Ca 11 concentration, because in the majority of platelets (.90%), fluorescence for NO was preceded by an intracellular Ca 11 increase, similarly to what was previously shown in smooth muscle cells 42 and endothelial cells. [43][44][45][46] The lag time between the 2 events in platelets (33 6 9.5 s) seems to be longer than that reported in vascular endothelial cells stimulated with bradykinin, in which a delay of ;5 seconds was observed, 45 or in human umbilical cord endothelial cells stimulated with histamine, 46 or in porcine aortic endothelial cells stimulated with thrombin, where almost no lag phase between the 2 events was observed.…”
Section: Blood 22 January 2015 X Volume 125 Number 4 Platelet Nitrisupporting
confidence: 49%
“…Given that a background DAF fluorescence was also present in unstimulated platelets in suspension and that some residual DAF fluorescence was observed in platelets adhering to collagen under flow after incubation with L-NMMA, it is possible that NO came in part from the reduction of inorganic nitrite within platelets. 41 We also showed that platelet NO production by individual platelets temporally follows the increase in cytosolic Ca 11 concentration, because in the majority of platelets (.90%), fluorescence for NO was preceded by an intracellular Ca 11 increase, similarly to what was previously shown in smooth muscle cells 42 and endothelial cells. [43][44][45][46] The lag time between the 2 events in platelets (33 6 9.5 s) seems to be longer than that reported in vascular endothelial cells stimulated with bradykinin, in which a delay of ;5 seconds was observed, 45 or in human umbilical cord endothelial cells stimulated with histamine, 46 or in porcine aortic endothelial cells stimulated with thrombin, where almost no lag phase between the 2 events was observed.…”
Section: Blood 22 January 2015 X Volume 125 Number 4 Platelet Nitrisupporting
confidence: 49%
“…6 In line with this, inorganic nitrite and nitrate have been shown to inhibit platelet aggregation. 14,17,48,49 On the basis of our current data, showing that esomeprazole interferes with nitrite-or nitrate-mediated effects on blood pressure, it would be interesting to evaluate whether PPIs will also influence the ability of these anions to modulate platelet function. Importantly, in this study, we only looked at one of the parameters known to be affected by nitrate and nitrite, and it remains to be determined whether other effects, including metabolic effects, are also dependent on gastric acidity.…”
Section: Discussionmentioning
confidence: 99%
“…In platelets, NO is one of the main vascular factors responsible for the inhibition of platelet activation (7,8). Once NO is produced, despite its short half-life, it diffuses in the plasma and smooth muscle and acts as a signaling molecule through activation of soluble guanylate cyclase (sGC) (9). sGC activation catalyzes the formation of the second messenger cGMP and subsequent inhibition of intracellular calcium release, resulting in decreased platelet aggregation.…”
mentioning
confidence: 99%